2010
DOI: 10.1016/j.pmrj.2010.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Poster 146: The Reliability of the Clinical Diagnosis in Persons Offered Surgery for Lumbar Spinal Stenosis

Abstract: Disclosures: M. Fredericson, Coolsystems, Inc, Consulting fees or other remuneration. Objective: To test the hypothesis that measures of patellar maltracking, tilt, and bisect offset, correlate with vastus medialis onset delays in patellofemoral pain (PFP) subjects classified as maltrackers. Design: Post hoc cohort study. Setting: Three-dimensional motion analysis laboratory, magnetic resonance (MR) imaging laboratory. Participants: 55 subjects: 15 healthy controls and 40 subjects with patellofemoral pain (PFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The relationship between radiological stenosis and clinical symptoms has been seriously challenged by a number of studies 47. A recent study has shown important disagreement between expert surgeons as to the presence of neurogenic claudication among persons who have been offered surgery for spinal stenosis 48. However in keeping with current convention, a clinical diagnosis of LSS, including presence of neurogenic claudication, with anatomical stenosis confirmed on MRI, was used.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between radiological stenosis and clinical symptoms has been seriously challenged by a number of studies 47. A recent study has shown important disagreement between expert surgeons as to the presence of neurogenic claudication among persons who have been offered surgery for spinal stenosis 48. However in keeping with current convention, a clinical diagnosis of LSS, including presence of neurogenic claudication, with anatomical stenosis confirmed on MRI, was used.…”
Section: Discussionmentioning
confidence: 99%